Nigeria Development Update, December 2020 : Rising to the Challenge - Nigeria's COVID Response - World Bank (World Bank, Washington, DC, 2020)
This report highlights how the COVID-19 (coronavirus) crisis has impacted Nigeria’s economy. In 2020, Nigeria’s economy is expected to experience its deepest recession since the 1980s due to the COVID-19-related disruptions, notably lower oil prices and remittances, enhanced risk aversion in global capital markets, and mobility restrictions. In the baseline scenario—which assumes further macroeconomic reforms and a gradual recovery in oil prices—Nigeria’s gross domestic product (GDP) is projected to contract by about 4 percent in 2020, growing modestly by 1.1 percent in 2021, and then recovering gradually towards the estimated population growth rate of 2.6 percent. With the rate of economic growth remaining below the population growth rate, per-capita incomes would continue declining and better full-time jobs will be much harder to find. This edition of the Nigeria Development Update takes stock of the recently implemented reforms and proposes policy options to both mitigate the impact of COVID-19 and foster a resilient, sustainable, and inclusive recovery. Managing the current crisis while strengthening the institutional and policy framework will require carefully sequenced reforms implemented over the immediate- and near-term. Robust mitigation and recovery policies would be based on five pillars: 1. Managing the domestic spread of COVID-19 until a vaccine is distributed; 2. Enhancing macroeconomic management to boost investor confidence; 3. Safeguarding and mobilizing revenues; 4. Reprioritizing public spending to protect critical development expenditures; and 5. Supporting economic activity and access to services and providing relief for poor and vulnerable communities.